分式化简 b/(a^2-ab)+2/(b-a)-a/(b^2-ab)

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/20 07:27:31
分式化简 b/(a^2-ab)+2/(b-a)-a/(b^2-ab)

分式化简 b/(a^2-ab)+2/(b-a)-a/(b^2-ab)
分式化简 b/(a^2-ab)+2/(b-a)-a/(b^2-ab)

分式化简 b/(a^2-ab)+2/(b-a)-a/(b^2-ab)
b/(a^2-ab)+2/(b-a)-a/(b^2-ab)
=b/a(a-b)-2/(a-b)+a/b(a-b)
=(b²-2ab+a²)/ab(a-b)
=(a-b)²/ab(a-b)
=(a-b)/ab

b/(a^2-ab)+2/(b-a)-a/(b^2-ab)
= b/[a(a-b)]-2/(a-b)+a/(ab-b^2)
= b/[a(a-b)]-2/(a-b)+a/[b(a-b)]
= b^2/[ab(a-b)]-2ab/[ab(a-b)]+a^2/[ab(a-b)]
=(b^2-2ab+a^2)/[ab(a-b)]
=(a-b)^2/[ab(a-b)]
=(a-b)/ab

原式=b/a(a-b)-2/(a-b)+a/b(a-b)
=(b²-2ab+a²)/ab(a-b)
=(a-b)²/ab(a-b)
=(a-b)/ab